Alih Kode dan Campur Kode dalam Pembelajaran Ushul Fiqh di Kulliyatul Mu’allimin Al-Islamiyah Pondok Pesantren Ibadurrohman Baleendah (Kajian Sosiolinguistik) - Sabrina, Coriena Halwa; Akmaliyah, Akmaliyah; Rohanda, Rohanda (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2025)
The purpose of the study was to determine the types of code switching and code mixing as well as the factors that cause code switching and code mixing in Ushul Fiqh Learning at Kulliyatul Mu'allimin Al-Islamiyah Islamic Boarding School Ibadurrohman Baleendah. This research uses descriptive qualitative method, data collected through listening and recording techniques on data sourced from recordings of the learning process of Ushul Fiqh learning at Kulliyatul Mu'allimin Al-Islamiyah Islamic Booarding School Ibadurrohman Baleendah. Data in the form of conversations between teachers and students in learning Ushul Fiqh at Kulliyatul Mu'allimin Al-Islamiyah Islamic Boarding School Ibadurrohman Baleendah. The results of this study indicate that code switching contained in Ushul Fiqh learning at Kulliyatul Mu'allimin Al-Islamiyah Ibadurrohman Islamic Boarding School Baleendah is external code switching. Code switching is in the form of switching from Arabic to Indonesian or from Indonesian to Arabic. The main cause of code switching is the speaker's desire to explain the material in a way that is easier for students to understand, and so that interlocutors who are familiar with the term can understand. While the code mix contained in Ushul Fiqh learning at Kulliyatul Mu'allimin Al-Islamiyah Ibadurrohman Islamic Boarding School Baleendah is code mixing outer. In the form of Arabic mixed with Indonesian or vice versa Indonesian mixed with Arabic. The factor that causes this code mix is because of the speaker’s habits in daily communication.